2021
DOI: 10.3389/fncel.2021.624648
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Signaling in Dendritic Development and Disease

Abstract: Dendrites undergo extensive growth and remodeling during their lifetime. Specification of neurites into dendrites is followed by their arborization, maturation, and functional integration into synaptic networks. Each of these distinct developmental processes is spatially and temporally controlled in an exquisite fashion. Protein kinases through their highly specific substrate phosphorylation regulate dendritic growth and plasticity. Perturbation of kinase function results in aberrant dendritic growth and synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 242 publications
(300 reference statements)
1
17
0
Order By: Relevance
“…In addition to these roles for CaMKII in Hebbian plasticity and learning, CaMKII is important for structural plasticity at dendritic spines. Here, CaMKII interacts with the dendritic cytoskeleton to drive spine enlargement 49 , 50 . Finally, CaMKII serves as a scaffold to promote the assembly of signaling machinery in dendrites 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these roles for CaMKII in Hebbian plasticity and learning, CaMKII is important for structural plasticity at dendritic spines. Here, CaMKII interacts with the dendritic cytoskeleton to drive spine enlargement 49 , 50 . Finally, CaMKII serves as a scaffold to promote the assembly of signaling machinery in dendrites 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Synapse‐associated proteins, particularly synaptophysin and PSD‐95, are hallmarks of synaptic plasticity and play a vital part in memory (Nourbakhsh & Yadav, 2021). Studies have confirmed that the protein level of synaptophysin and PSD‐95 in 19‐month‐old mice were significantly down‐regulated compared with 3‐month‐old mice (Vazquez‐Roque et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the kinase domain is highly conserved, these three TAO kinases have divergent C-terminal tails that confer them with specific and distinct functions. Both TAOK1 and TAOK2 are associated with neurodevelopmental disorders (Nourbakhsh and Yadav, 2021). Recently, we identified TAOK2 as a transmembrane kinase that tethers the endoplasmic reticulum to microtubules (Nourbakhsh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%